2020
DOI: 10.1111/jpc.15132
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences Should Be Priority in Global Response to Covid‐19

Abstract: Available from: https://www.moh.gov. sg/docs/librariesprovider5/diseases-updates/childhood-immunisation-2017d0b895c2b9464bfd9296deb0cf73e709.pdf [accessed 15 August 2019] 3 Lee PPW. Disseminated Bacillus Calmette-Guérin and susceptibility to mycobacterial infections-Implications on Bacillus Calmette-Guérin vaccinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Recent findings related to COVID-19 and historical research show that the mental health fallout from COVID-19 will disproportionately impact those already vulnerable in society [65][66][67][68]. This study supports previous research showing that those who have experienced ACE report greater psychological distress over time during the current COVID-19 pandemic [25,26,32,36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recent findings related to COVID-19 and historical research show that the mental health fallout from COVID-19 will disproportionately impact those already vulnerable in society [65][66][67][68]. This study supports previous research showing that those who have experienced ACE report greater psychological distress over time during the current COVID-19 pandemic [25,26,32,36].…”
Section: Discussionsupporting
confidence: 85%
“…Early research has indicated that those who experienced ACEs are more vulnerable to both the direct and indirect effects of COVID-19, than those without [26,27,[32][33][34][35][36][37][38][39]. In addition, those with several ACEs (i.e., ≥4) are more likely than individuals without ACEs to have existing mental health difficulties, chronic physical ill-health, and are disproportionately from lower socioeconomic backgrounds [21,25,28,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty associated with the pandemic, the angst experienced both on a personal and a social level, has for some children been an adverse childhood experience (ACE). [ 4 , 5 ] At time goes on for countries emerging from the pandemic, we will begin to see the visible and invisible scars the syndemic has been left behind.…”
Section: T He S Ocial C ...mentioning
confidence: 99%
“…To counter the increasing number of viruses spread, the government moved quickly to protect the world of education, namely by the policy of distance learning. With this policy, digital media becomes the center of learning because direct interaction will be limited and new habituation related to online learning models must be done immediately by teachers and parents at home [2]. The pattern of education conducted at home must also meet the standards of health protocols so that children can carry out their learning activities comfortably [3].…”
Section: Introductionmentioning
confidence: 99%